STUDI PENERAPAN SISTEM AKUSTIK PADA RUANG KULIAH AUDIO VISUAL - Indrani, Hedy C.; Cahyawati, Citra (Dimensi Interior, 2011)
A good audio visual lecture hall is a space designed with the right systems for the room itself, especially in terms of the application of interior acoustics. The acoustic conditions of audio visual lecture halls are often designed without real consideration and thus result in acoustic reverberation and feedback when used. Manual calculation, Autodesk Ecotect Analysis 2011 software, and Armstrong Reverberation software were the methods and tools used in this research. Results indicated that the use of material that have a low absorption coefficient such as concslab on ground, framed plywood partition, single glazed alum frame blinds, and solid core oak timber could meet the standard acoustic level for audio visual rooms appropriate for speech.